Malaysia Workforce Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
Malaysia s technical and vocational training (TVET) program is born out of a combination of ambition and necessity. The country has recorded impressive economic growth over several decades, bolstering ambitions that it should make the transition from middle- to high-income by transforming to a knowledge (K) economy. Vision 2020, announced by then Prime Minister Mahathir Mohamad, was to give substance to this plan. The need to make this transformation was driven home by a deceleration of this growth after the Asian Financial Crisis at the turn of the century followed by the Global Financial Crisis a decade later and has galvanized the country s leaders to action to bolster its human capital. TVET can play an important role in Malaysia s transformation to a knowledge economy.